Contraceptive Discontinuation and Method Switching among Women in La Nkwantanang Madina Municipal Area - Appiah, E.T. (University of Ghana, 2019)
Introduction: The increase in contraceptive knowledge does not correlate with user uptake and fertility decline. Majority of women are knowledgeable about contraceptives and its benefits, however, few women are using it. Method discontinuation or switching after adoption has increased among women. Since the pattern of a women’s contraceptive use has a direct impact on fertility and population growth, it is imperative that population control programs target them to ensure consistency in needed contraception. Objectives: The objectives of the study were to assess factors that contribute to contraceptive method discontinuation and method switching among women in La Nkwantanang Madina Municipal Area. Method In depth interviews were conducted among fifteen women in the reproductive age attending family planning clinics who had either discontinued use or switched methods. They were selected from two health facilities within the La Nkwantanang Madina municipality. Data was analysed using thematic content analysis. Results: Study findings revealed that factors such as side effects of contraceptives and lack of access to contraceptives influence contraceptive discontinuation and switching of methods. This study identified that young women are more likely to stop use than their older counterparts. It was also observed that majority of the participants switched from long acting to short acting methods. The most commonly used method by the participants was the implant. Conclusion: Most women switch between methods due to method related difficulties. Majority of them discontinue use due to side effects, when they no longer need the contraceptive and when access to the health facility proves difficult. It is recommended that public health education on effectiveness of the various contraceptives be strengthened in order to control switching or discontinuing use of adopted contraceptive methods. Routine follow ups on clients should also be ensured.
MPH.
Keywords: Contraceptive; Adolescent; La Nkwantanang Madina Municipal Area